Primary Lymphoma of the Central Nervous System. Case Presentation - Julio Dámaso Fernández Águila; Yanisleidys Valladares Urquiza; Martha Yudey Rodríguez Pino; Icilany Villares Álvarez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Primary Lymphomas of the Central Nervous System are an uncommon variety of non- Hodgkin extra node which may affect the brain, spinal cord, eyes, meninges and cranial nerves. It is presented a case of a 51-year-old patient who came to the doctor complaining of headache and papilledema caused by an encephalic lesion was corroborated which required surgical treatment. Histological study allowed diagnosing a non-hodking lymphoma of a high malignancy, B cells, positive CD20, with a type of peripheral Burkitt pattern. The patient received immunochemo-therapy and radiotherapy, with a favorable evolution. Because it is an uncommon and aggressive tumor it was decided to present the case.